Saw the office, want the job: The effect of creative workspace design on organizational attractiveness. (April 2022) - Maier, Lukas; Baccarella, Christian V.; Wagner, Timm F.; Meinel, Martin; Eismann, Tobias; Voigt, Kai-Ingo
Abstract: Attracting talent is key for every organization. This research introduces a novel way to attract talent: creative workspace design. In two studies with complementary samples and methods, we examine whether, when, and how a firm's creative workspace design enhances organizational attractiveness. In Study 1, we use an experimental design to examine the attraction effect of creative (vs. conventional) workspace design from the applicant's perspective. First and foremost, we find that creative workspace design has a positive effect on organizational attractiveness. Second, our findings reveal two underlying mechanisms that help to explain this positive attraction effect: perceived climate for creativity and perceived innovation ability of the firm. Moreover, findings show that this attraction effect is stronger for highly creative (vs. less creative) individuals and attenuated for high-value (vs. low-value) workspaces. In Study 2, we validate the positive attraction effect of creative workspace design from the firm's perspective by using international survey data on a firm level. Taken together, this work sheds new light on how workspace design influences organizational attractiveness, elucidates why and when applicants are attracted by creative workspace design, and provides actionable implications for practice. Highlights: Firms' creative (vs. conventional) workspace design positively influences applicants' job choice intentions. Two inferences help explain this attraction effect: perceived climate for creativity and innovation ability of the firm. The positive attraction effect is stronger for applicants with high (vs. low) creative personal identity. The positive attraction effect is attenuated for high-value (vs. low-value) workspaces.